Temat polityczny w sztuce krytycznej na przykładzie Fear and Trembling Grzegorza Klamana - Lorenc, Magdalena (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The objective of the paper is to emphasize political themes as inspiration for artists and an interpretational key for the works of so-called critical art, based on the example of Fear and Trembling by Grzegorz Klaman from 2007. The analysis concerns the installation and its exhibition context of the third review of modern art, Mediations Biennale, entitled Niepojmowalne/The Unknown, held in Poznań, Poland, from September 14 to October 14, 2012. Fear and Trembling refers to Søren Kierkegaard’s book by the same title from 1843. The issue tackled by the Danish philosopher, and referred to by the Polish artist, concerns the relation between ethics and faith. Klaman’s installation is a form of statement about a reality where one’s religious outlook has a bearing on one’s political decisions and can lead to armed conflict. Examples of religious arguments used in order to justify violence are provided, among others, by the history of the Arab-Israeli conflict over Palestine.
Political themes in critical art based on the example of Grzegorz Klaman’s Fear and Trembling